2015
DOI: 10.1120/jacmp.v16i3.4959
|View full text |Cite
|
Sign up to set email alerts
|

Potential of 3D printing technologies for fabrication of electron bolus and proton compensators

Abstract: In electron and proton radiotherapy, applications of patient‐specific electron bolus or proton compensators during radiation treatments are often necessary to accommodate patient body surface irregularities, tissue inhomogeneity, and variations in PTV depths to achieve desired dose distributions. Emerging 3D printing technologies provide alternative fabrication methods for these bolus and compensators. This study investigated the potential of utilizing 3D printing technologies for the fabrication of the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 24 publications
2
77
0
2
Order By: Relevance
“…This has been demonstrated through the use of 3D‐printers in the fabrication of bolus, compensators, and patient‐specific phantoms . Thus far, most 3D‐printed boluses have been used for small and/or relatively flat treatment sites, such as the nose, ear, eye canthi, and foot surface . Additionally, most 3D‐printed bolus has used standard, rigid thermoplastic materials, including polylactic acid and acrylonitrile butadiene styrene.…”
Section: Introductionmentioning
confidence: 99%
“…This has been demonstrated through the use of 3D‐printers in the fabrication of bolus, compensators, and patient‐specific phantoms . Thus far, most 3D‐printed boluses have been used for small and/or relatively flat treatment sites, such as the nose, ear, eye canthi, and foot surface . Additionally, most 3D‐printed bolus has used standard, rigid thermoplastic materials, including polylactic acid and acrylonitrile butadiene styrene.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the advantages of electron conformal therapy performed using customized 3D-printed electron boluses and compensators over that performed with conventional ones [7, 8, 11, 12]. However, since these studies used the 3D-printed boluses only on phantoms and did not provide details of the procedures used, there remained a lack of information regarding their use with actual patients.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Zou et al [8] reported that 3D printers have the ability to fabricate compensators with much finer patterns. As this trends, Park et al [9] used the 3D-printed bolus for Kimura's disease as a case report.…”
Section: Introductionmentioning
confidence: 99%
“…The bolus substance must be odorless, non-sticky, and harmless to the skin. In this study, thus, the polylactic acid (PLA) was adopted as a bolus material [16, 17]. We printed a patient-specific breast bolus for an anthropomorphic phantom and simulated a real patient treatment.…”
Section: Introductionmentioning
confidence: 99%